Hydrogels From Tradition to Innovative Platforms with Multiple Applications - Popa, Lăcrămioara; Violeta Ghica, Mihaela; Dinu-Pîrvu, Cristina-Elena (IntechOpen, 2023)
Hydrogels are well-defined structures that do not dissolve in water. They have many uses, especially in biomedicine. This book provides a comprehensive overview of hydrogels, including their characteristics and applications in medical devices, drug delivery, robotics, "smart" applications, and more.